Characteristics of Chitosan from Black Soldier Fly Pupa Shells as a Crosslinking Agent in the Manufacture of Slow-Release Fertilizer Hydrogels - Sri Wahyuna Saragih; Wardatul Husna Irham; Ingrid Ovie Yosephine; Muhammad Ferza; Bella Yulia; Annisah Fadhilah (Jurnal Penelitian Pendidikan IPA, 2025)
Chitosan, a natural polysaccharide obtained through the deacetylation of chitin, exhibits unique properties that make it a potential material for various applications, including agriculture. This study aims to examine the characteristics of chitosan derived from Black Soldier Fly (BSF) pupa shells and its role as a crosslinking agent in polymer-based hydrogel synthesis for slow-release fertilizers. Chitosan was isolated through chemical processes, including demineralization, deproteinization, and deacetylation. Characterization was conducted using FTIR, XRD, SEM, TEM, and TGA. The results revealed that chitosan from BSF pupa shells has a degree of deacetylation of 83%, a semi-crystalline and slightly amorphous structure, pores that enhance water absorption capacity, and high thermal stability. These properties make chitosan an effective crosslinking agent, improving hydrogel stability and extending nutrient release duration. These findings demonstrate the potential of chitosan as an innovative material for hydrogel applications in sustainable agriculture.